Risk Factor Analysis Of Low Birth Weight Events (Lbw) At Kartika Husada Hospital - Santi Herawati; Feva Tridiyawati (International Journal of Health and Pharmaceutical (IJHP), 2023)
WHO and UNICEF data, in 2013 around 22 million babies were born in the world, of which 16% of them were born with low birth weight babies. Indonesia ranks third as a country with the highest prevalence of LBW (11.1%), after India (27.6%) and South Africa (13.2%). In addition, Indonesia is also the second country with the highest prevalence of LBW among ASEAN countries, after the Philippines (21.2%). The impact of LBW on babies is at risk for degenerative diseases, and babies will experience mental disabilities if the baby experiences a lack of nutrition for a long time. Knowing the analysis of risk factors for low birth weight events. Analytical with a cross-sectional design. The sample in this study was 95 babies born at Kartika Husada Hospital Bekasi in January-June 2021 (systematic random sampling). Most pregnant women did not give birth to low birth weight babies (69.5%), aged 20-35 years (89.5%), did not have preeclampsia (94.7%), gestational age 37-42 weeks (76.8%), and did not KPD (84.2%). There is a relationship between maternal age, pre-eclampsia, gestational age and KPD with the incidence of LBW at Kartika Husada Bekasi Hospital in 2022 (p. value <0.005).There is a relationship between maternal age, pre-eclampsia, gestational age and KPD with the incidence of LBW at Kartika Husada Bekasi Hospital in 2022. It is hoped that pregnant women will try to prevent the occurrence of KPD which can cause the birth of LBW babies.